Transformed by Christ and Liberation from Discrimination: Reading John 4:1–41 in Ideological Criticism - Putri, Diana Kerenhapukh Eka (Program Pascasarjana UKIM, 2025)
This article explores John 4:1–41 through the lens of ideological criticism to reveal its liberative potential in resisting cultural constructs that marginalize women. The encounter between Jesus and the Samaritan woman at the well is examined as a counter-ideology that dismantles patriarchal norms of exclusion, stigma, and gender discrimination. By challenging socio-religious boundaries of ethnicity, gender, and morality, the narrative demonstrates Christ’s transformative power that affirms women’s dignity and agency. This study argues that the text not only exposes the oppressive ideologies embedded in its cultural setting but also offers a liberating vision in which women become active bearers of faith and witnesses to truth. Such a reading invites contemporary Christian communities to embody the same transformative ethos in confronting ongoing structures of discrimination today.